Investigating the molecular pathogenesis of tuberculosis-associated immune reconstitution inflammatory syndrome - Moseki, Raymond (Department of Medicine, 2025)
Thesis summary This thesis comprises a series of studies that adapted a reverse translational approach to investigate the mechanisms underlying the immunopathogenesis of paradoxical tuberculosis associated immune reconstitution inflammatory syndrome (TB-IRIS). Paradoxical TB-IRIS is an aberrant immune response targeted against Mycobacterium tuberculosis or its residual antigens in patients with advanced human immunodeficiency virus (HIV) infection shortly after commencement of antiretroviral therapy (ART). TB-IRIS is characterized by hyperinflammation and tissue damage. Pulmonary and lymph node involvement are the most common clinical manifestations. The incidence of TB-IRIS can reach up to 54% in settings where both HIV and TB are endemic, such as the sub-Saharan-Africa region of the African continent. Approximately 25% of patients with paradoxical TB-IRIS will require hospitalization for syndromic management. The management and prevention of paradoxical TB-IRIS rely on the use of anti-inflammatories such as immunosuppressive corticosteroid intervention, which is associated with an increased risk of Kaposi sarcoma. Paradoxical TB-IRIS is potentially fatal, with cases of central nervous system (CNS) involvement having the highest fatalities (up to 56%). The underlying cause of paradoxical TB-IRIS is thought to arise from a dysregulated hyperinflammatory immune response during ART-mediated immune recovery, although the causal mechanisms and associated molecular pathways are incompletely defined. This knowledge gap compromises efforts to develop new diagnostic and prognostic modalities as well as safer and more efficacious therapeutic interventions. This served as the rationale for undertaking the studies reported in this thesis. Using clinical samples from the PredART intervention trial and the TB-ART observational study, this thesis investigated the cellular and molecular determinants of paradoxical TB-IRIS. Conventional scientific hypothesis-based approaches as well as unbiased hypothesis generating approaches were used, with major experimental approaches including ribonucleic acid (RNA) sequencing, flow cytometry and soluble analyte analyses. RNA extracted from whole blood of consenting participants from the Pred-ART intervention trial was sequenced to profile global gene expression. Cross-sectional and longitudinal analyses were performed to compare transcriptomic profiles in participants who developed paradoxical TB-IRIS to those who did not, at week 0, 2 and 12 on ART. Using pathway analysis, samples collected prior to the initiation of ART (week 0) in patients who later developed paradoxical TB-IRIS (cases) were characterized by the upregulation of transcripts encoding neutrophil-derived antimicrobial peptides and defensins and associated with hypoxemia compared to the TB-non-IRIS controls. These largely reflected biological processes involved in neutrophilic responses and adaptation to metabolic stress and dysfunction. Furthermore, pathways that were significantly downregulated in patients who later developed paradoxical TB-IRIS compared to those who did not, included chondroitin sulfate biosynthesis and interleukin (IL)-6. These finding suggest that paradoxical TB-IRIS is preceded by increased expression of antimicrobial peptides and the impairment of immune cellular function controlled by the extracellular matrix. Pathway analysis at week 2 on ART, which coincided with the median time of clinical manifestations in patients that developed paradoxical TB-IRIS, revealed the significant enrichment of neutrophil degranulation, interleukin (IL)-1 signalling, as well as type I and II interferon (IFN). Moreover, biological pathways that were significantly downregulated in cases as opposed to controls at week 2 on ART were largely overrepresented by epigenetic biological processes. These data suggested that neutrophil degranulation preceded and characterized the onset of paradoxical TB-IRIS. To validate these findings, we evaluated the associations between absolute neutrophil counts and neutrophil soluble markers, with paradoxical TB-IRIS at week 0 and week 2 on ART. No significant differences in absolute neutrophil counts were reported in participants who later developed paradoxical TB-IRIS compared to those who did not at week 0. However, azurocidin measured in plasma samples by enzyme-linked immunosorbent assay (ELISA) was significantly lower in samples from participants who later developed paradoxical TB-IRIS at week 0. This suggests that participants who are likely to develop paradoxical TB-IRIS might have impaired innate immune responses at week 0 compared to those who did not develop the syndrome. Absolute neutrophil counts were higher in cases compared to controls at week 2 on ART. Soluble neutrophil markers including human neutrophil peptide 1-3, myeloperoxidase, and neutrophil elastase were significantly higher in cases compared to controls at week 2 on ART. These data suggest that patients who develop paradoxical TB-IRIS have heightened neutrophil degranulation at the time of symptoms onset. Longitudinal perturbation of gene expression was investigated between week 0 and week 2 in people who developed paradoxical TB-IRIS and TB-non-IRIS controls, respectively. Among the top significantly upregulated biological pathways in samples of participants that developed paradoxical TB-IRIS were neutrophil degranulation, type I and II interferon signaling, IL-1 cytokine signalling, and pyroptosis. Biological pathways that were significantly downregulated in these patients included heme biosynthesis and oxygen-carbon dioxide gaseous exchange signalling metabolic dysfunction. In TB-non-IRIS controls, biological pathways that were significantly upregulated included epigenetic modulation of gene expression, collagen biosynthesis and extracellular cytoskeleton remodelling indicating anabolic processes that restore or maintain proper cellular functionality such as cellular signalling. Type I interferon signalling and immune responses to viral pathogens were among biological pathways that were significantly downregulated in people who did not develop paradoxical TB-IRIS at week 2 on ART compared to week 0, likely indicating decrease in antiviral responses as HIV viral load declined. The management and prevention of paradoxical TB-IRIS rely on the use of corticosteroids which is associated with an increased risk of Kaposi Sarcoma and herpes reactivations. Thus, there is a need to explore other anti-inflammatory but non-immunosuppressive drugs that can be repurposed for the management of IRIS-related pathologies. Gene expression data at week 2 on ART and previous published data indicated that aberrant inflammasome activation represent one of the molecular mechanisms that underpins the pathogenesis of paradoxical TB IRIS. We proposed that chemical inhibition of the inflammasome would result in a targeted reduction of inflammation. Two candidate drugs (anakinra and parthenolide) were evaluated and benchmarked against the standard of care (prednisolone) in an ex vivo mycobacterial cell stimulation model using patient samples. Both anakinra and parthenolide significantly reduced several markers of inflammation compared to prednisolone. However, parthenolide was the more potent in reducing cytokine production including IL-1 among others. These findings provide experimental evidence of in vitro use of novel anti-inflammatory agents. Anakinra has been approved for clinical use in inflammatory conditions such as rheumatoid arthritis and could potentially be repurposed for use in the context of paradoxical TB-IRIS. A hallmark of paradoxical TB-IRIS includes the partial reconstitution of Mtb-specific CD4 T cell responses within 3 months of initiating ART while on effective antituberculosis therapy. The phenotype and transcription factors of antigen-specific interferon-gamma producing (IFN+) CD4+ T cells and their potential involvement in the pathogenesis of paradoxical TB IRIS were characterized in an experimental mouse model of IRIS (by collaborators) as well as in human peripheral blood mononuclear cells (PBMC). In mice, antigen-specific CD4 T cells knocked out for Eomes showed significantly higher proportion of survival compared to wildtype mice. No significant differences in Eomes expression were observed in Mtb-300 specific, IFN+ CD4 T cells in PBMC from paradoxical TB-IRIS cases compared to controls at the onset of clinical symptoms. However, Eomes expression was higher in cases compared to controls in bulk CD4 T cells at week 2 on ART. HLA-DR expression was higher in cases compared to controls in Mtb300-specific IFN+ CD4 T cells at week 2 on ART. Additionally, Granzyme B producing, Mtb300-specific IFN+ CD4 T cells co-expressing Eomes and Tbet were significantly higher in cases compared to controls at week 2 on ART. These data indicate that HLA-DR expression on Mtb300-specific CD4 T cells producing IFN+ can potentially be developed as a diagnostic tool to identify individuals with paradoxical TB-IRIS. Collectively, these findings highlight the key contribution of neutrophils and Mtb-specific CD4 lymphocytes in the pathogenesis of paradoxical TB-IRIS. The gene expression findings suggest that the underlying mechanism involves interferon stimulated genes which trigger the secretion of proinflammatory cytokines and the aberrant activation of the inflammasome. Members of the IL-1 family of cytokines are secreted as catalytically inactive proenzymes that require the action of mature inflammasome for activation. IL-1a is the only exception since its proform and mature form are both fully functional. Active IL-1 family of cytokines are potent modulators of inflammation which is a defining feature in people who develop paradoxical TB-IRIS at the time of clinical symptom onset. In addition, the pathogenesis of paradoxical TB-IRIS appears to be mediated by the heightened degranulation of neutrophils which may cause acute inflammation and tissue damage.